The Meaning of Determining Indekos 'Tariffs' from the Indekos Owner's Perspective - INDRIASARI, Rahayu; BAKRY, Moh Iqbal; MAPPARESSA, Nurlaela; PARWATI, Ni Made Suwitri; JURANA, Jurana; DHARMA, Dewa Made Adi (Journal of Tourism Economics and Policy, 2023)
This research aims to understand and interpret the meaning of "Determining Boarding House Rates from the owner's perspective during the COVID-19 pandemic among boarding house entrepreneurs in Central Sulawesi. This research uses the Interpretive Paradigm of the Transcendental Phenomenological Approach. Interviews, Observations, and Documentation were used to collect research data. This is important to reveal the shift in the meaning of determining tariffs in situations that make it difficult for owners to adopt boarding house income tariff policies. The results of this research indicate that for boarding house owners, the costs incurred in owning a boarding house are routine costs at all times. Therefore, for them, the meaning of determining the boarding fee is a manifestation of gratitude for the excellent fortune given by God Almighty. The determination of these rates manifests the boarding house owner's struggle in facing the COVID-19 pandemic. Apart from that, determining the tariff is also interpreted as a form of brotherly feeling of helping each other. This then forms a rationality of thought for boarding house entrepreneurs who use this feeling of joy and happiness as a trigger for determining boarding house rates and providing reductions in tariff determination.